2019
DOI: 10.3390/vetsci6020041
|View full text |Cite
|
Sign up to set email alerts
|

Volatilome in Milk for Grana Padano and Parmigiano Reggiano Cheeses: A First Survey

Abstract: Milk characteristics in terms of volatile compounds can influence the subsequent product characteristics and can give indications about metabolism. These features can strongly depend on feeding and management. In this perspective, the screening of milk samples intended for Parmigiano-Reggiano and Grana Padano located in Northern Italy was performed, focusing on a panel of volatile molecules. The work was carried out on a total number of 25 bovine milk samples for the production of Parmigiano-Reggiano and Grana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Different studies have already demonstrated the possibility of the utilization of fatty acids profile from dairy products not only to identify the type of feeding system (daily rations of fresh grass vs. no fresh grass in the diet) [31][32][33][34][35][36], but also to ensure geographical authentication of the protected designation of origin dairy products [37]. However, despite the breed consistency increasing importance in last years, no studies have considered the possibility to distinguish between dairy products of Original Brown cows grazing or not on Italian alpine pastures.…”
Section: Introductionmentioning
confidence: 99%
“…Different studies have already demonstrated the possibility of the utilization of fatty acids profile from dairy products not only to identify the type of feeding system (daily rations of fresh grass vs. no fresh grass in the diet) [31][32][33][34][35][36], but also to ensure geographical authentication of the protected designation of origin dairy products [37]. However, despite the breed consistency increasing importance in last years, no studies have considered the possibility to distinguish between dairy products of Original Brown cows grazing or not on Italian alpine pastures.…”
Section: Introductionmentioning
confidence: 99%
“…A further filter was applied to each resulting OTU table to remove entries having less than 5 reads and binning them to unassigned (UN). Out of the assigned reads for each sample, entries representing more than 1% of the reads of a sample were labelled as “dominant” [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…In fact, DNA has higher stability compared to other biological markers, such as proteins, and can be isolated even in matrices with extremely low contents [13][14][15]. In this regard different studies have been described for enhancement of GP or other dairy products: Rocchetti et al (2018) [16] outlined a metabolomic approach to ensure the authenticity of GP, Faustini et al (2019) [17] reported on a volatilome study on milk destined to the production of both GP and Parmigiano Reggiano cheeses and, metabarcoding of bacterial communities has been used for the preservation and valorisation of similar food products [18][19][20]. Several studies have shown that feed-derived plant nuclear and/or chloroplast DNA fragments can also be detected in milk [21].…”
Section: Introductionmentioning
confidence: 99%